Legal Sanctions against Soldiers of Kodim 0304/Agam in Online Gambling Crimes - Saputra, Edi; Munandar, Syaiful (Hakamain: Journal of Sharia and Law Studies, 2026)
This study aims to analyze the application of legal sanctions against soldiers of Kodim 0304/Agam involved in online gambling crimes and to examine the legal mechanisms used in handling such cases within the framework of military law enforcement. The increasing involvement of military personnel in cyber-based gambling activities has raised concerns regarding legal accountability, military discipline, and institutional integrity. This research employs an empirical legal research method with a qualitative approach through field research, document analysis, and the examination of relevant legal regulations governing military and criminal law. Data were collected through interviews, observations, and supporting legal documents related to the implementation of sanctions for military personnel involved in online gambling activities. The findings indicate that soldiers involved in online gambling crimes are subject not only to criminal sanctions under applicable laws but also to disciplinary sanctions and administrative measures under the military justice system. The imposition of sanctions is influenced by the nature of the offense, the degree of involvement, and institutional considerations related to maintaining military discipline and public trust. The study finds that legal enforcement in military institutions prioritizes both punitive and corrective dimensions to preserve professional conduct among soldiers. This study concludes that the application of legal sanctions against soldiers involved in online gambling requires an integrated legal approach combining criminal responsibility and military disciplinary principles. The academic contribution of this research lies in expanding the discourse on military criminal law and providing a contextual understanding of legal accountability for online gambling offenses within military institutions.